2021
DOI: 10.31436/imjm.v20i2.1640
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D and Cardiometabolic Markers: A Comparative Study in Adult Men Based on Body Mass Index

Abstract: INTRODUCTION: Deficiency of vitamin D has been implicated in several disorders, including skeletal, immune, neural, metabolic, and cardiovascular diseases (CVDs). The impact of vitamin D deficiency on CVDs is potentially through derangement of cardiometabolic profile. The present work assessed the relationship between serum vitamin D levels and cardiometabolic markers in adult men. MATERIALS AND METHODS: A cross-sectional analytical study (n=160) was conducted on adult men between the ages 35-50 years without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Vitamin D, a fat-soluble secosteroid hormone, is a key contributor to musculoskeletal health through its role in calcium and phosphorus homeostasis [1]. Data accrued over the last two decades has shown that low vitamin D levels are associated with a wide range of clinical disorders such as immune dysfunction, cardiovascular diseases, autoimmunity, and neurological deficits, suggesting the involvement of vitamin D in multiple physiological processes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D, a fat-soluble secosteroid hormone, is a key contributor to musculoskeletal health through its role in calcium and phosphorus homeostasis [1]. Data accrued over the last two decades has shown that low vitamin D levels are associated with a wide range of clinical disorders such as immune dysfunction, cardiovascular diseases, autoimmunity, and neurological deficits, suggesting the involvement of vitamin D in multiple physiological processes [2].…”
Section: Introductionmentioning
confidence: 99%
“…In our elderly population which is significantly deficient in Calcium and Vitamin D3 and thus more prone to early onset osteoporosis 9 . In international studies the outcome showed that PHILOS plate gives maximum fracture stabilization in the treatment of proximal humeral fractures of old age.…”
Section: Introductionmentioning
confidence: 88%
“…Hydrogen has been found to have anti-inflammatory, anti-allergenic, and anti-apoptotic properties in biomedical research (i.e., programmed cell death) [215]. The use of hydrogen in the treatment of rheumatoid arthritis, brain stem infarction, diabetes mellitus, neurodegenerative illnesses, cancer, and exercise-or sportsinduced oxidative stress are among the other therapeutic applications of hydrogen that have been established [216][217][218][219][220][221][222][223][224]. Hydrogen is a physiological and metabolic regulating component that regulates protein phosphorylation and gene expression [225].…”
Section: Futuristic Hydrogen Applicationsmentioning
confidence: 99%